The prevalence of antimicrobial resistance of bacterial strains from large-scale healthy chicken flocks in the Észak-Alföld region of Hungary - Kerek, Ádám; Szabó, Ábel; Barnácz, Franciska; Csirmaz, Bence; Jerzsele, Ákos (Frontiers in Veterinary Science, 2026)
IntroductionAntimicrobial resistance (AMR) represents one of the major public health challenges of the 21st century, with profound implications for both human and veterinary medicine. Isolates recovered from clinically healthy birds from food-producing animals play a critical role as reservoirs and potential vectors for resistance genes, underscoring the importance of continuous surveillance. This study aimed to evaluate the phenotypic resistance profiles of Staphylococcus aureus, Enterococcus spp. and Escherichia coli isolated from large-scale chicken flocks in the Észak-Alföld region of Hungary.MethodsA total of 24 flocks were sampled, and bacterial isolates were subjected to antimicrobial susceptibility testing using the broth microdilution method. Minimum inhibitory concentrations (MICs) were interpreted according to European Committee on Antimicrobial Susceptibility Testing (EUCAST) and Clinical Laboratory Standard Institute (CLSI) guidelines.ResultsExtremely high (>70.0%) levels of resistance were detected against doxycycline, amoxicillin, and florfenicol, while resistance to critically important antimicrobials such as ceftriaxone, imipenem and vancomycin remained comparatively low (1.0–10.0%) or rare (<0.1%). Multidrug resistance (MDR), defined as resistance to three or more antimicrobial classes, was observed in more than half of the isolates. Resistance patterns varied across farms, but amoxicillin and florfenicol resistance frequently co-occurred, serving as strong predictors of MDR status.DiscussionThese findings highlight the substantial prevalence of AMR among bacteria in intensive poultry systems in Hungary. The results emphasize the need for enhanced antimicrobial stewardship, prudent antibiotic use in livestock, and targeted biosecurity interventions to mitigate the potential spillover of resistance into the broader ecosystem and human health. While the species investigated are known to include pathogenic strains, the isolates analyzed in this study were obtained from healthy birds and are thus regarded as isolates recovered from clinically healthy birds’ representatives.